From a colonial reinvention to postcolonial heritage and a global commodity: performing and re-enacting Angkor Wat and the Royal Khmer Ballet - Falser, Michael (International journal of heritage studies, 2014)
It is a commonplace that cultural heritage is not only a highly contested concept of modern times, full of nationalistic undertones, cultural stereotypes and essentialist topoi such as past grandeur and enduring cultural purity. Cultural heritage has also become the easiest and most profitable prey for today’s global tourism industry. These observations apply with particularly dramatic consequences to young emerging, postcolonial nation states with a rich repertoire of built (tangible) and performed (intangible) culture - especially if elements of this repertoire are branded ‘UNESCO World Heritage’ without considering their contested formation histories. Few other iconic heritage sites are more instructive in showcasing these observations than the temple site of Angkor, by charting the transcultural trajectories of Cambodia’s heritage construction through the processes of French colonial reinvention, postcolonial/nationalist essentialisation, and global commodification. This paper focuses on the ‘Royal Khmer Ballet’ as cultural performance and heritage re-enactment in combination with the twelfth-century temple of Angkor Wat as architectural stage. References to similar ‘heritagisation’ processes in the (post)colonial Dutch East Indies (now Indonesia) will help to anchor this transcultural enquiry.
Published online: 24 May 2013
Gesehen am 25.09.2020